Impact of educational intervention on hypertension management by primary care physician: A randomized control trial - Tariq Ashraf; Kanwal Fatima Aamir; Asif Nadeem; Mahmood Ul Hassan; Haseeb Raza; M. Abdur Rauf; Jalal Ud Din; Saeedullah Shah; Fayza Khan; Zubair Akram; Muhammad Ishaque; Bashir Hanif (PEC Innovation, 2024)
Objective: The current study aimed to observe hypertension educational intervention's effect on general physicians (GPs) to improve blood pressure control and patient outcomes indirectly. Methods: This randomized control trial includes 42 GPs divided into 2 groups. GPs in group 1 receive face-to-face education with structured educational material on hypertension management strategies by a senior cardiologist. GPs in group 2 receive the print version of education material. The data was collected from six major cities in Pakistan. GPs with at least three years of experience in the broad primary care disciplines, with ages above 18 years, were included in the study. Results: A total of 42 physicians (21 from each group) completed questionnaires, while out of 420 hypertension patients, 105 newly diagnosed and already diagnosed patients enrolled under physicians of both groups. The educational material did just as well at informing clinicians as the face-to-face group intervention did and both the interventions had a significant effect on knowledge and BP control. Conclusion: After the 3-month follow-up, both interventions, including face-to-face and educational approaches, demonstrated significant effectiveness in improving knowledge and blood pressure control. Innovation: The study shows that hypertension educational intervention's effect on general physicians indirectly improves blood pressure control and patient outcomes. And emphasize for developing a hypertension educational program targeted at general physicians.